Analisis Permintaan Uang di Indonesia - Risma, Okta Rabiana (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the demand for money in a narrow sense (m1) in Indonesia using quarterly time series data from 2001 to 2013 against exchange rate variables and gross domestic product. The analysis method used is Autoregressive Distributed Lagged (ARDL). The results showed that the three variables did not have a cointegration caused by differences in order in their stationary tests. In the short term, the exchange rate (ER) and gross domestic product (GDP) have a significant influence on the demand for M1 money. In the long run, the exchange rate has a significant influence on the demand for M1 money. In the demand for M1 money in Indonesia, the central bank's policy through exchange rates is still very influential. Therefore, it is expected that price stability will be maintained through the exchange rate channel as one of the central bank's policy mechanisms. Keywords: ardl, cointegration, money demand.